Conversational Implicature In Netflix Sex Education Series: A Pragmatics Study - Hafidz Rahayu Khomaeni Arief Rahayu; Ervina CM Simatupang (Universitas Veteran Bangun Nusantara, 2026)
The research explores conversational implicature in Sex Education Season 1, Episode 5, focusing on how implied meanings reflect cultural heritage and improve teen communication. Using qualitative descriptive methods and Levinson’s pragmatics framework, the study analyzes transcripts to identify 21 instances of conversational implicature: 12 (57%) generalized, understood without specific context, and 9 (43%) particularized, relying on background knowledge. The main functions found are economy of expression (48%), contextual adaptation (29%), and social appropriateness (24%). These implicatures help characters communicate efficiently, adapt to social settings, and maintain politeness or indirectness, highlighting the social and cultural dynamics of adolescence. The study shows that conversational implicature is a key linguistic tool in the series, portraying the complexities of adolescent interaction and cultural identity in modern media. This research illustrates how pragmatic language use in popular culture both mirrors and shapes social interaction and identity development among youth.Keywords: Conversational Implicature, Pragmatics, Types CI, Generalized CI, Particularized CI